Airway mucosal inflammation in COPD is similar in smokers and ex-smokers: a pooled analysis. - Gamble, E; Grootendorst, D; Hattotuwa, K; O'Shaughnessy, T; Ram, F; Qiu, Y; Zhu, J; Vignola, A; Kroegel, C; Morell, F; Pavord, I; Rabe, K; et al. (2007)
Bronchial biopsy specimens from chronic obstructive pulmonary disease (COPD) patients demonstrate increased numbers of CD8+ T-lymphocytes, macrophages and, in some studies, neutrophils and eosinophils. Smoking cessation affects the rate of forced expiratory volume in one second (FEV(1)) decline in COPD, but the effect on inflammation is uncertain. Bronchial biopsy inflammatory cell counts were compared in current and ex-smokers with COPD. A pooled analysis of subepithelial inflammatory cell count data from three bronchial biopsy studies that included COPD patients who were either current or ex-smokers was performed. Cell count data from 101 subjects, 65 current smokers and 36 ex-smokers, were analysed for the following cell types: CD4+ and CD8+ T-lymphocytes, CD68+ (monocytes/macrophages), neutrophil elastase+ (neutrophils), EG2+ (eosinophils), mast cell tryptase+ and cells mRNA-positive for tumour necrosis factor-alpha. Current smokers and ex-smokers were similar in terms of lung function, as measured by FEV(1) (% predicted), forced vital capacity (FVC) and FEV(1)/FVC. The results demonstrate that there were no significant differences between smokers and ex-smokers in the numbers of any of the inflammatory cell types or markers analysed. It is concluded that, in established chronic obstructive pulmonary disease, the bronchial mucosal inflammatory cell infiltrate is similar in ex-smokers and those that continue to smoke.